The Influence of Leadership and Discipline on Employee's Performance in Bank Mandiri Branch Bogor - Dewi Maharani; Anwar Yuli; Hirayanti Hirayanti (Lembaga Penelitian, Pengembangan, dan Pengabdian Kepada Masyarakat (LP3M) – Universitas Binaniaga Indonesia (UNBIN), 2026)
The purpose of this research, is to know and to analyze the influence of leadership and discipline on employee performance both partially and simultaneously on the employee performance. The research method that is used is associative clausal. The number of populations in this research is 150 employees and the number of samples are 75 samples. The analysis technique is using multiple linier regression analysis. Based on the F Test, the leadership and discipline have a simultaneous influence to the employee’s performance in Bank Mandiri Branch Bogor with the score of F Count>F Table (569>3, 18). Based on the T Test, it shows that the leadership and discipline bring a significant influence to the employee’s performance in Bank. Mandiri Branch Bogor. With the T Count > T Table (10,046>1.662) with the significant rate 0,000<0,005. Based on the Coefficient Determination Analysis, the Adjusted R Square is 0,600 or 60%.